2009
DOI: 10.1002/elan.200904609
|View full text |Cite
|
Sign up to set email alerts
|

FTIR‐ATR Study of Water Uptake and Diffusion Through Ion‐Selective Membranes Based on Plasticized Poly(vinyl chloride)

Abstract: In this paper, the water uptake and diffusion of water through ion-selective membranes based on plasticized poly(vinyl chloride) (PVC) have been studied by FTIR-ATR spectroscopy. The diffusion of water was modeled by the finite-difference method and the obtained diffusion coefficients are reported for membranes plasticized with bis(2-ethylhexyl) sebacate (DOS) and 2-nitrophenyl octyl ether (oNPOE). The influence of various common membrane additives such as lipophilic salts and ionophores on the water uptake wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 42 publications
2
93
2
1
Order By: Relevance
“…We found that it is better to make the potential adjustment of the SCs before 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 Water uptake of the PPy-PFOS solid contact. The water uptake of plasticized PVC-ISMs has been recently characterized by the FTIR-ATR spectroscopy 29,30,68 and the oven based coulometric Karl Fischer titration technique. 68 It was shown that water diffuses readily through the PVC-ISMs and that the water content of the membrane is influenced by the chemical composition of the electrolyte solution contacting the ISM.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that it is better to make the potential adjustment of the SCs before 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 Water uptake of the PPy-PFOS solid contact. The water uptake of plasticized PVC-ISMs has been recently characterized by the FTIR-ATR spectroscopy 29,30,68 and the oven based coulometric Karl Fischer titration technique. 68 It was shown that water diffuses readily through the PVC-ISMs and that the water content of the membrane is influenced by the chemical composition of the electrolyte solution contacting the ISM.…”
Section: Chemicalsmentioning
confidence: 99%
“…[18][19][20][21] The role of the SC is to provide a stable inner phase boundary potential 20,22,23 at the substrate/SC and SC/ISM interfaces, and to prevent the aqueous layer formation at the inner interface, which coupled to diffusion of ionic species within the ISM may lead to potential instability. 24 As all ISMs exhibit water uptake [25][26][27][28][29][30][31] , the prevention of the aqueous layer formation 32,33 with ill-defined ion activity has proven to be a major challenge.…”
mentioning
confidence: 99%
“…Among the techniques used here, ATR gives us information about the "in-situ" processes that occur in the membrane phase. In other reports, ATR-IR was primarily used for monitoring water penetration into the liquids membranes, but rarely for monitoring reaction processes within membranes [14][15][16][17][18][19]. Other techniques such UV-Vis cyclic voltammetry and potentiometry were used for validating the proper functioning of the proposed sensor.…”
Section: Introductionmentioning
confidence: 98%
“…The transparency of plasticized PVC is altered by light scattering caused by water penetration when ions are extracted into the bulk of the PVC. 24,25 Hence, the specific peak spectra of PhC based on light diffraction and interference, strength of diffraction light was decreased. This is because, the light scattering directly reflects the decrease in diffraction intensity.…”
Section: Evaluation Of the Phc-based Optode Membrane Ion Sensor Contamentioning
confidence: 99%